Mother’s Curse effects on lifespan and aging - Edmands, Suzanne (Frontiers in Aging, 2024)
The Mother's Curse hypothesis posits that mothers curse their sons with harmful mitochondria, because maternal mitochondrial inheritance makes selection blind to mitochondrial mutations that harm only males. As a result, mitochondrial function may be evolutionarily optimized for females. This is an attractive explanation for ubiquitous sex differences in lifespan and aging, given the prevalence of maternal mitochondrial inheritance and the established relationship between mitochondria and aging. This review outlines patterns expected under the hypothesis, and traits most likely to be affected, chiefly those that are sexually dimorphic and energy intensive. A survey of the literature shows that evidence for Mother's Curse is limited to a few taxonomic groups, with the strongest support coming from experimental crosses in Drosophila. Much of the evidence comes from studies of fertility, which is expected to be particularly vulnerable to male-harming mitochondrial mutations, but studies of lifespan and aging also show evidence of Mother's Curse effects. Despite some very compelling studies supporting the hypothesis, the evidence is quite patchy overall, with contradictory results even found for the same traits in the same taxa. Reasons for this scarcity of evidence are discussed, including nuclear compensation, factors opposing male-specific mutation load, effects of interspecific hybridization, context dependency and demographic effects. Mother's Curse effects may indeed contribute to sex differences, but the complexity of other contributing factors make Mother's Curse a poor general predictor of sex-specific lifespan and aging.